A Self-Regulatory Model For The Management Of The Environment And Public Issues In Marine Mining - Julian Malnic (International Marine Minerals Society, 2000)
The emerging marine minerals exploration and mining industry is currently focused mainly on the technical elements for its success such as developing exploration and mining technologies. However, in one sense, the technical challenges are quite soluble whereas those arising in the fields of the environment and public opinion could present this new generation of miners with problems that are far more difficult to overcome. One need only look at the issues currently faced by mining projects on land to see how powerful the new forces of so-called ?civil society? are in stopping mineral developments in many countries. From the geographic viewpoint, there are many countries but there is just one ocean, so the impacts experienced by any one operation are likely to have pervasive repercussions throughout the industry. A well-oiled NGO development protest lobby will see leverage in resisting this new industry and will seize on the single-ocean angle. The Australian Minerals Industry has established a voluntary Code for Environmental Management that provides an active and valuable model for satisfying the ?court of public opinion? and in delivering economic results to industry that are in current jargon, sustainable. An explanation of the Code for Environmental Management, and the reasons behind 44 companies representing more than 300 operations and 85% of Australia?s sizeable mineral production being signatory to it will be given. Participants see it as a means to future shareholder wealth.